(untitled) (MAUSAM, 2003)
Teleconnections between mid latitude circulation over different sectors and onset of Indian summer monsoon over Kerala for the period of 1971-89 have been examined. Significant negative relationships are observed between the meridional circulation indices and general perturbation of zonal flow and the monsoon onset over Kerala. Strong and significant positive relationships are also observed between frequency of zonal index over sector 160° E to 45° W and onset dates of monsoon over Kerala.